1995
DOI: 10.1016/s0006-3495(95)79990-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms determining the strength of receptor-mediated intermembrane adhesion

Abstract: The strength of receptor-mediated cell adhesion is directly controlled by the mechanism of cohesive failure between the cell surface and underlying substrate. Unbinding can occur either at the locus of the specific bond or within the bilayer, which results in tearing the hydrophobic anchors from the membrane interior. In this work, the surface force apparatus has been used to investigate the relationship between the receptor-ligand bond affinities and the dominant mechanism of receptor-coupled membrane detachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 20 publications
(71 reference statements)
11
91
0
Order By: Relevance
“…5). Such an effect is in accordance with the low forces required to extract phospholipids [30,58], the recovering protein anchored to the membrane via a myristic acid [24] and BIAP [21] from a bilayer. The extraction force required might also differ between fluid and ordered phases and, in our experience, could occur in both contact and oscillating modes.…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainssupporting
confidence: 67%
“…5). Such an effect is in accordance with the low forces required to extract phospholipids [30,58], the recovering protein anchored to the membrane via a myristic acid [24] and BIAP [21] from a bilayer. The extraction force required might also differ between fluid and ordered phases and, in our experience, could occur in both contact and oscillating modes.…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainssupporting
confidence: 67%
“…We observed this behavior in five independent experiments with three separate protein preparations. The reproducibility both of the force curves and of the adhesion measured after initial detachment also showed that the lipid anchors did not pull out of the membrane (29). This indicates that rupture indeed occurred at the protein-protein contacts.…”
Section: Definition Of the Intersurface Separation Distance Dmentioning
confidence: 72%
“…In all previous force measurements of protein-ligand interactions, bond failure results in the abrupt snap of the molecules out of adhesive contact (14,15,(25)(26)(27)(28)(29)(30)(31)(32). By contrast, the cadherin unbinding profile (Fig.…”
Section: Definition Of the Intersurface Separation Distance Dmentioning
confidence: 91%
“…Thus, streptavidin/biotin-mediated targeting of virosomes to liposomes specifically depended on simultaneous interaction of streptavidin with virosomal and liposomal biotin. The virosome and liposome membranes which fuse in this study are separated by the diameter of the streptavidin molecule, which is about 4.5 nm [16]. The interesting relationship between this distance and the extent of fusion may be investigated further by the use of lipophilic biotin ligands with spacers of different lengths.…”
Section: Kinetics and Specificity Of Streptavidin/biotin-mediated Fusionmentioning
confidence: 92%